The applicability of the European GMO legislation to epigenetically modified organisms - Faltus, Timo (Frontiers in Bioengineering and Biotechnology, 2023)
In addition to classic genetic engineering for the targeted modification of the base sequence of the DNA, epigenetic methods for the targeted modification of the genetic material without base changes are increasingly being used. Such epigenetic techniques can be used, for example, to influence stress tolerance to heat or aridity in plants. The regulatory handling of organisms generated by means of epigenetic techniques on the grounds of genetic engineering law has not yet been clarified. This paper critically reviews the legal classification of epigenetically modified organisms as GMOs as expressed in the study on New Genomic Techniques published in April 2021 by the European Commission. The paper shows that there are reasons to assume that epigenetically modified organisms are not covered by the European GMO legislation. In addition, the paper provides an introductory overview of the significance of epigenetics and the methods used to intentionally influence epigenetic traits and illustrates the possibility for a consistent, risk-based regulation of epigenetic modifications.